Enhanced breast cancer cell targeting: RGD integrin ligand potentiates RWQWRWQWR’s cytotoxicity and inhibits migration - Andrea Barragán-Cárdenas; Daniel Castellar-Almonacid; Yerly Vargas-Casanova; Claudia Parra-Giraldo; Adriana Umaña-Pérez; Joel López-Meza; Zuly Rivera-Monroy; Javier García-Castañeda (Exploration of Drug Science)
Aim: Evaluate the selective cytotoxic effect of the palindromic sequence RWQWRWQWR and its analogues obtained by replacement of L-amino acids by D-amino acids or the functionalization by adding the RGD (integrin ligand motif) to the peptide. Methods: Peptides were obtained by SPPS, characterized by RP-HPLC and ESI-QTOF and its biological activity was evaluated using MTT assays. Evaluation of mechanism associated to the cytotoxic effect were carried out by flow cytometry, RT-qPCR, wound healing, transwell and zymography. Results: The peptides with replacements of D-amino acid showed a lesser cytotoxic effect against breast cancer cell lines, regardless it was one or several residues modified which suggested a possible specific interaction between the peptide and the cancer cell membrane besides its initial electrostatically contact. On the other hand, addition of the RGD sequence to the palindromic peptide in the N-terminal end resulted in a greater cytotoxic effect against cell lines derived from the three mainly diagnosed breast cancer molecular subtypes. An approximation on mechanisms associated to this effect was evaluated on MCF-7 cells, it shows that the peptide induced apoptosis by activating intrinsic and extrinsic pathway, which correlates with the possibility of a specific interaction, and induces mitochondrial depolarization with release of oxygen reactive species. Also, this peptide induces a reduction in migration and invasion associated with a diminish in metalloprotease 9 activity and a lesser release of IL-6, IL-10 and arginase cytokines. Conclusions: Our results suggest that this promising peptide can be considered for preclinical evaluation in the development of drugs to treat breast cancer and thus mitigate the impact of this disease.